Association Between the Weight-Adjusted Waist Index and OSA Risk: Insights from the NHANES 2017–2020 and Mendelian Randomization Analyses [Corrigendum] - Wang H; Yang B; Zeng X; Zhang S; Jiang Y; Wang L; Liao C (Nature and Science of Sleep, 2025)
Wang H, Yang B, Zeng X, et al. Nat Sci Sleep. 2024;16:1779–1795. The authors have advised that there is an error in affiliation 1 on page 1779. The text “Clinical Medical College, Chengdu University of Traditional Chinese Medicine” should read “Hospital of Chengdu University of Traditional Chinese Medicine”. The authors apologize for this oversight.